Gambaran Perasaan Insecure di Kalangan Mahasiswa yang Mengalami Kecanduan Media Sosial Tiktok - Agresta Armando Harnata; Berta Esti Ari Prasetya (Bulletin of Counseling and Psychotherapy, 2022)
TikTok is one of the results of advances in the world of technology that can make it easier for someone to do anything online. It is not surprising that most people today use various social media to disseminate the information they get, both in groups and individually. The purpose of the study is to get an overview of the feelings of insecurity among Satya Wacana Christian University psychology students who are addicted to TikTok social media, as well as the factors that affect insecurity that cause feelings of insecurity among Satya Wacana Christian University psychology students who are addicted to TikTok social media. This type of research is qualitative research with a phenomenological research design. Data collection in this study used interviews and observations of 3 participants. This study uses technical triangulation and time triangulation as a test of the credibility of the data. From the results of this study, it was found that the insecurity of the Satya Wacana Christian University psychology faculty students felt anxious and nervous about their own appearance, as well as a feeling of lack of confidence in their abilities. There are factors that affect the insecurity of Satya Wacana Christian University psychology students, namely comparing their work too much and comparing their physical appearance to other people who are more famous.